4-formyl dibenzo-18-crown-6 grafted polyvinyl alcohol as anion exchange membranes for fuel cell. (March 2019) - Zheng, XuYing; Song, ShiYang; Yang, JiaRui; Wang, JiLin; Wang, Lulu
Graphical abstract: Highlights: 4-formyl dibenzo-18-crown-6 (FDB18C6) was synthesized. DB18C6 was added in polyvinyl alcohol (PVA). The crown ether cation was successfully used as anion conducting groups. Anionic conductivity of membranes was increased. The membranes comply with the requirements of fuel cell. Abstract: 4-formyl dibenzo-18-crown-6 (FDB18C6) was synthesized through dibenzo-18-crown-6 (DB18C6), and it was added into polyvinyl alcohol (PVA) through acetal reaction to form a new type of membrane (FX% -P). Then the FX% -P membranes were immersed into the KOH solution to prepare FX% -P-K membranes, which through the complexation of crown ion on K + . The complex crown ether cation was successfully applied as anion conducting groups. The characterization and experimental results showed that FX% -P-K membranes had already successfully synthesized, and possess better anionic conductivity and alkali resistance stability compared with other anion exchange membranes (AEMs). The water uptake and swelling ratio of F20% -P-K membrane was reduced to 25.0% and 14.5%, separately, suppressed effectively the excessive swelling of PVA. And the dimensional stability of F20% -P-K was 21.1%, which reflected excellent membrane stability. In addition, especially outstanding performance was the anionic conductivity of FX% -P-K membranes increased from 7.63 mS·cm −1 to 25.32 mS·cm −1 at 70 °C, which confirmed excellent anionic conductive ability. After alkali treatment of preparing membranes, the conductivity degradation rate is less than 8.6% reflected superb alkali resistance. The aforementioned results defined that the FX% -P-K membranes comply with the requirements in the anion exchange membrane fuel cell.